Identification of Plasminogen in MatrigelTM and Its Activation by Reconstitution of This Basement Membrane Extract. (November 1996) - Farina, A.R.; Tiberio, A.; Tacconelli, A.; Cappabianca, L.; Gulino, A.; Gulino, A.; Mackay, A.R.
Matrigel TM, a basement membrane (BM) extract of the Engelbreth-Holm-Swarm (EHS) sarcoma, used in tumor invasion assays, was found to contain plasminogen. Plasminogen was identified, using Western blot analysis and casein zymograms, by comparison with human plasminogen. Matrigel contained approximately 20–100 ng of plasminogen per 100 μg of protein as determined by these assays. Matrigel reconstitution and incubation at 37°C caused activation of plasminogen, which was serine protease dependent and involved tissue plasminogen activator (tPA) as an anti-tPA antibody which inhibited activation. This reconstitution and incubation also caused leupeptin-inhibitable degradation of Matrigel components as assessed by sodium dodecyl sulfate polyacrylamide gel electrophoresis. Degradation of the BM extract copolymerized in zymograms was caused by human plasminogen and plasminogen in the Matrigel. Maximal plasmin activity, following incubation of Matrigel at 37°C for 16 h, was equivalent to approximately 10 ng of purified plasmin using the plasmin substrated -Val-Leu-Lys p-nitroanilide. Matrigel, therefore, contained all the components of the plasmin-generating system, including plasminogen. The plasmin generated degraded Matrigel components and exogenous substrates. Our data suggest that, since this tumor BM acts as a reservoir for enzymes of the plasmin-generating system, caution should be taken by investigators interpreting data concerning the effects of Matrigel on cell behavior and, in particular, cellular invasion.